Implementation of Good Corporate Governance (GCG) Principles in Improving Company Performance in Indonesia - Nada Adista Rambe; Adelia Salsabila Marbun; Ahmad Asri Nasution; Ahmad Deedad; Taufik Hidayat Batubara (Jurnal Sahabat ISNU SU, 2025)
This study aims to analyze the implementation of Good Corporate Governance (GCG) principles in Indonesian companies and assess their effectiveness in improving corporate performance and accountability. GCG implementation is becoming increasingly important with the increasing demands for transparency, accountability, and corporate social responsibility. This study uses a normative-juridical approach and a literature review method, reviewing legal literature, laws and regulations, scientific journals, and reports on GCG implementation in various companies. A descriptive-analytical approach is used to describe the actual conditions of GCG implementation and assess its impact on corporate governance. The results show that although regulations governing GCG principles exist in Indonesia, their implementation still faces various challenges, such as weak management commitment, a lack of understanding of GCG principles, and minimal external oversight. This study recommends the need for regulatory strengthening, increased GCG literacy among business actors, and an active role from supervisory institutions in supporting the creation of good and sustainable corporate governance.